Strategi Pemasaran Mobil Konvensional dan Mobil Listrik Di Pasar Indonesia - Rayhan Arief Widitya; Fachrizal Satrio Putro Yuwono; Mohamad Zein Saleh (Universitas 45 Surabaya, 2024)
The purpose of this research is to analyze the marketing strategies of conventional cars and electric cars in the Indonesian market. The research method is a literature study and comparative analysis of the marketing strategies of conventional cars and electric cars in the Indonesian market. The results of this study show significant differences in marketing strategies between the two types of cars. In conventional car marketing, commonly used strategies include television advertisements, promotions from authorized dealers, and participation in automotive exhibitions. On the other hand, electric car marketing tends to use a more environmentally conscious approach, focusing on sustainability and green technology. Strategies include clean energy promotion, participation in green events, and collaboration with environmental organizations. The high price of electric cars and limited charging infrastructure are major obstacles to the marketing of electric cars in Indonesia. However, there are significant opportunities to grow the electric car market through consumer education, improved charging infrastructure, and co-operation with government, industry, and communities.